Polysemy and Homonymy of Derivational Morphemes in the Modern Armenian Language - Felekyan, Manuk (Bulletin of Yerevan University B: Philology, 2024)
The main criterion for differentiating the polysemy and homonymy of suffixes is their semantics: all meanings of polysemous suffixes contain the same semantic invariant. Homonymous suffixes do not have any semantic connection. Another important criterion is the ability of the suffix to be combined with various word-forming stems, as well as the part-of-speech affiliation of the newly formed word. The origin of suffixes should be considered only as an aid to distinguishing homonyms.
Keywords: homonymy of morphemes; polysemous suffixes; homonymous suffixes; variants of suffixes; word-formation basis; semantic invariant; criteria for distinguishing polysemy and homonymy